Flavonoids from Limau Peel (Citrus amblycarpa (Hassk.) Ochse) and Their Antioxidant Activity - Kristin Shinta Dewi; Euis Julaeha; Kindi Farabi; Unang Supratman (Molekul, 2022)
Citrus amblycarpa (Hassk.) Ochse is an endemic Indonesian plant from West Java. This study aims to determine the chemical structure of the flavonoid compounds of C. amblycarpa peel ethanol extract and their antioxidant activity. Three flavonoid compounds, namely 5-hydroxy-3',4',6,7,8-pentamethoxyflavone (1), 8-hydroxy-3,3',4',5,6,7-hexamethoxyflavone (2), and 3',4',5,6,7,8-hexamethoxyflavone (3), were isolated for the first time from the ethanol extract of C. amblycarpa peel. Their chemical structure was determined by spectroscopic methods (MS, IR, 1H-NMR, 13C-NMR, and DEPT) and compared with previous reported spectral data. Furthermore, these compounds were evaluated for their antioxidant activity using the DPPH method. The results showed that 8-hydroxy-3,3',4',5,6,7-hexamethoxyflavone (2) has the highest antioxidant activity with IC50 value of 121.09 ± 0.24 ppm.